Medical Record Folder Redesign - WD Sitti Apria; Ahmad Amiruddin; Wa Ode Sitti Budiaty (International Journal of Multidisciplinary Learners, 2024)
Medical record folder function to protect and organize medical record forms so that they are not scattered. This folder should be made of strong materials, such as manila or ivory, to ensure the security and durability of documents containing confidential information. Redesign of medical record folders at bungi health center using the methods used in documentation studies and interviews. Redesign of medical record folders at bungi health center is needed to improve the durability and longevity of the folder. By using stronger materials and the right design techniques, medical record folders can be protected from damage such as tearing or shattering, so that important information remains safe and easy to access. This can also increase administrative efficiency and provide convenience for medical staff in managing patient data. This study aims to redesign the design of medical record folders according to the theory and needs of the health center. Using a case study method, the subject of the study was the head of the medical record installation, while the object was the medical record folder itself. Data analysis was carried out descriptively. The results of the study showed that the redesign of medical record folders paid attention to physical aspects, using 260 gram ivory material to improve quality and functionality. The results of the medical record map design are expected to be a practical solution to improve the efficiency and quality of medical record services at the Bungi Healthy Center. With a design that suits your needs, this map can facilitate document management, speed up access to patient information, and support access to patient information, and support medical staff in providing better services. The implementation of this design is expected to increase patient satisfaction and work effectiveness at the health center.